The Role of Entrepreneurial Self-Efficacy in Mediating the Effect of Entrepreneurship Education and Financial Support on Entrepreneurial Behavior - Ida Bagus Agung Dharmanegara; Putu Laksmita Dewi Rahmayanti; Ni Nyoman Kerti Yasa (Universitas Pendidikan Ganesha, 2022)
In college, the willingness of students to start or run a business is still relatively low. This study aimed to analyze the role of entrepreneurial self-efficacy in mediating the effect of entrepreneurship education and financial support on entrepreneurial behavior. This research is a type of causality research. Data collection was continued by distributing questionnaires in Google Form to several WhatsApp groups. This study's population is active university students who already have online businesses in Bali. The sample size used is 210 respondents with the purposive sampling method. The analytical technique used is Path Analysis using SEM-PLS. The results showed that entrepreneurship education positively and significantly affected entrepreneurial behavior. Financial support also has a positive and significant effect on entrepreneurial behavior. Furthermore, entrepreneurship education has a positive and significant effect on entrepreneurial self-efficacy; financial support also has a positive and significant effect on entrepreneurial self-efficacy, and entrepreneurial self-efficacy affects entrepreneurial behavior. In addition, entrepreneurial self-efficacy can mediate the effect of entrepreneurship education and financial support on online business entrepreneurial behavior.